Unanthribus, um novo gênero Neotropical de Ptychoderini Jekel, 1855 (Coleoptera, Anthribidae, Anthribinae) - Mermudes,José Ricardo M. (2003)
Unanthribus gen. nov. is proposed to include Unanthribus maximus sp. nov. (type species) described from Brazil (Pará), and U. grandis (Jordan, 1911) comb. nov., which is redescribed. The species are illustrated and keyed.